Structural and Physicochemical Characteristics of Granular Malic Acid-Treated Sweet Potato Starch Containing Heat-Stable Resistant Starch - Chinwoo Kwon; Ha Ram Kim; Tae Wha Moon; Seung Hyun Lee; Chang Joo Lee (Journal of Chemistry)
This study investigated the structural and physicochemical characteristics of malic acid-treated sweet potato starch. Sweet potato starch mixed with various concentrations of malic acid solution underwent either thermal or nonthermal treatment. Observation of samples under a light microscope ensured the maintenance of granular shape and the Maltese cross. FT-IR spectra displayed a distinct carbonyl peak at 1722 cm−1, and analysis of the degree of substitution (DS) indicated an increase in the extent of ester bonds with increasing concentrations of malic acid. The DS of 2.0M-130 (0.214) was the highest and that of 0.5M-130 was the lowest (0.088) among the reacted starches. In vitro digestion test revealed an increased amount of resistant starch when a high concentration of malic acid was used. In addition, thermally treated samples maintained a higher content of resistant starch (RS) after 30 min of cooking at 100°C. After cooking, 2.0M-130 had an RS fraction of 53.4% which was reduced to 49.9% after cooking, revealing greater heat stability compared with nonthermally treated samples. The structure of malic acid-treated starch was investigated using a differential scanning calorimeter (DSC), an X-ray diffractometer, a rapid visco analyzer (RVA), and analysis of apparent amylose content. The results showed that thermal and malic acid treatment of starch caused not only partial hydrolysis but also rearrangement of the crystalline area and helix structure of starch by esterification. Analysis of malic acid-treated starch, using a rapid visco analyzer showed no pasting properties, due to lack of its swelling caused by the malic acid cross link.